THE SITUATION IN PRACTICE OF IMPROVING THE METHODOLOGICAL PREPARATION OF THE DEVELOPMENT OF NATURAL SCIENCES COMPETENCES IN PRIMARY CLASS STUDENTS - Kholiqova Farida (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the advantages of using interactive methods, case study method, brainstorming, and small group work methods in the STEAM education system.